Mandibular second molar with 3 mesial canals and a radix paramolaris - N Ragavendran; Ganesh T Bhat; Mithra N Hegde (Wolters Kluwer Medknow Publications, 2014)
Mandibular first molar commonly has two roots, the mesial and the distal root. Surprisingly in some mandibular first molar has an unusual extra third root in between mesial and distal root. This extra root is the most commonly seen in lingual side and is called as radix entomolaris. If this extra root is seen on the buccal side, it is termed as radix paramolaris (RP), which is a very rare phenomenon. Recently, various case report studies has shown the presence of third canal in the mesial and distal roots of mandibular molars. They are named as middle mesial and middle distal canal, respectively. Here, we present a case report of mandibular second molar showing three canals in the mesial root and a RP.